Intérêt de la lyophilisation pour améliorer la stabilité des microémulsions charges en Amphotéricine B destinées au traitement de la leishmaniose - Morais, Andreza Rochelle do Vale (2017)
Visceral leishmaniasis is a neglected tropical disease that can be fatal if left untreated. Amphotericin B (AmB) is effective in the treatment of this disease, but the conventional formulation, Fungizone® has dose-limiting toxicity while the less toxic lipid-based forms such as Ambisome® are expensive. Therefore, the need for new therapeutic systems remains. In this respect, the heating of the Fungizone® formulation (H-AmB), and the development of a microemulsion (ME) containing AmB (MEAmB) are possible solutions. In addition, it is desirable to remove water from microemulsion systems in order to reduce instability due to microbiological contamination and hydrolysis. Therefore, the objective of this work was to develop and to evaluate the activity and toxicity in vitro and in vivo of H-AmB and MEAmB against Leishmania donovani (strain LV9) and, furthermore, to optimize a lyophilized microemulsion system containing AmB. Rheological, size and morphology studies showed that MEAmB presented average droplet sizes of 35 nm, a Newtonian behavior and spherical morphology. Spectroscopic characterization of H-AmB showed the formation of superaggregates, which are less toxic than the other states of aggregation. In-vitro evaluation on both the axenic and intramacrophagic amastigote forms showed that H-AmB and MEAmB showed similar activity to Ambisome®. A high selectivity index of H-AmB and MEAmB was observed compared with unheated Fungizone®. Furthermore, both new formulations showed high activity against AmB-resistant strains compared with Ambisome®. In-vivo experiments designed to evaluate their activity and toxicity did not reveal significant differences in activity between the new and reference formulations. There were no significant differences either in indicators of renal and hepatic toxicity. Therefore, both H-AmB and MEAmB can be used as an alternative for the treatment of LV9, presenting an advantage over AmBisome® in their lower costs of production. Therefore, a complete experimental design was performed in order to optimize the lyophilisation of the microemulsion system. It was observed that microemulsions with smaller droplet sizes were obtained using maltose as a cryoprotectant at a concentration of 5%, with freezing at -80 ° C, and a lyophilization process period of 24 h. Furthermore, it was observed that ME containing AmB showed no significant changes in drug content before and after the lyophilization process. Therefore, in its lyophilized form, the ME can remain stable and avoid degradation due to the presence of water.